Likelihood of Surgery in Isolated Pediatric Fifth Metatarsal Fractures. Issue 3 (April 2015) - Mahan, Susan T.; Hoellwarth, Jason S.; Spencer, Samantha A.; Kramer, Dennis E.; Hedequist, Daniel J.; Kasser, James R.
Abstract : Background: Fractures of the fifth metatarsal bone are common and surgery is uncommon. The "Jones" fracture is known to be in a watershed region that often leads to compromised healing, however, a "true Jones" fracture can be difficult to determine, and its impact on healing in pediatric patients is not well described. The purpose of this study was to retrospectively assess patterns of fifth metatarsal fracture that led to surgical fixation in an attempt to predict the likelihood for surgery in these injuries. Methods: A retrospective review was performed on patients aged 18 and under who were treated for an isolated fifth metatarsal fracture from 2003 through 2010 at our pediatric hospital. Patient demographics, treatment, and complications were noted. Radiographs were reviewed for location of fracture and fracture displacement. Patients and fracture characteristics were then compared. Results: A total of 238 fractures were included and 15 were treated surgically. Most surgical indications were failure to heal in a timely manner or refracture and all patients underwent a trial of nonoperative treatment. Jones criteria for fracture location were predictive of needing surgery ( P <0.01) but confusing in the clinic setting. Fractures that occurred between 20 and 40 mm (or 25% to 50% of overall metatarsal length) from the proximal tip went on to surgery in 18.8% (6/32) of the time, whereas those that occurred between <20 mm had surgery in 4.9% (9/184). This was a statistically significant correlation ( P =0.0157). Conclusions: Although fractures of the fifth metatarsal are common, need for surgery in these fractures is not. However, a region of this bone is known to have trouble healing, and it can be difficult to identify these "at-risk" fractures in the clinical setting. We found simple ruler measurement from the proximal tip of the fifth metatarsal to the fracture to help determine this "at-risk" group and found a significant difference in those patients with a fracture of <20 mm compared with those 20 to 40 mm from the tip; this can help guide treatment and counsel patients. Level of Evidence: Level 3.